Control of the electrode metal transfer by means of the welding current pulse generator; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Knyazkov A. F. Anatoly Fedorovich; Пустовых О. С. Ольга Сергеевна; Verevkin A. V. Aleksey Valerievich; Shachek A.; Knyazkov S. A. Sergey Anatolievich; Tyasto A. (Materials Science in Mechanical Engineering, 2016)
Title screen